Synthesis of nanopolycrystalline mesoporous diamond from periodic mesoporous carbon: Mesoporosity increases with increasing synthesis pressure. (15th March 2019) - Najiba, Shah; Juhl, Stephen J.; Mandal, Manik; Liu, Cong; Durygin, Andriy; Chen, Jiuhua; Fei, Yingwei; Alem, Nasim; Landskron, Kai
Abstract: We report the catalyst-free synthesis of monolithic mesoporous nanopolycrystalline diamond from periodic mesoporous carbon at pressures between 15 and 21 GPa and a temperature of 1300 °C. We investigated the pressure-dependence of the porosity with 3-dimensional electron tomography. We have observed that surface areas increase from 56 to 90, 138 m 2  g −1, and porosities increase from 10, 24, to 33% for materials produced at 15, 18, and 21 GPa, respectively. The increased porosity at higher pressure may be due to the earlier onset of the nucleation of diamond at higher pressure. Graphical abstract: Unlabelled Image